Decarbonization in Complex Energy Systems: A Study on the Feasibility of Carbon Neutrality for Switzerland in 2050 - Li, Xiang; Damartzis, Theodoros; Stadler, Zoe; Moret, Stefano; Meier, Boris; Friedl, Markus; Maréchal, François (Frontiers in Energy Research, 2020)
Decarbonization gained prominence with the witnessed rise of temperature over recent years, particularly in the aftermath of the adoption of the Paris agreement for limiting the temperature increase within 2°C until 2050. Biogenic resources are explicitly indicated as carbon-neutral from Life Cycle Assessment perspective by the IPCC, shedding light on the carbon-neutral society by applying Biogenic Energy Carbon Capture for creating negative emissions. This article proposes a novel modeling approach by introducing carbon layers with specification on the principal carbon sources and sinks based upon an optimization algorithm, in order to solve the carbon loop issue in a highly interconnected energy system due to increasing penetration of biomass and carbon capture, use, and storage. This study contributes to quantifying biogenic and nonbiogenic carbon footprints, and optimizing the circular economy associated with a net-zero-emission society, in favor of policy-making for sustainable development in long terms.